Usage of Phase Change Material as Heat Storage in Water Desalination - Leony Serenauli Pandjaitan; Muhamad Dwi Septiyanto; Syamsul Hadi (Universitas Sebelas Maret, 2026)
Phase Change Material (PCM) refers to substances that can absorb or release heat, making them effective for heat storage applications. PCMs can be categorized by chemical composition into three primary types: organic, inorganic, and eutectic. In Indonesia, a nation characterized by extended periods of sun exposure, selecting the most suitable PCM for solar still desalination experiments poses a challenge in reducing inefficient practical outcomes. This study investigates the properties of various PCMs and analyzes the essential factors to consider when choosing a PCM for heat storage. The research employs a review method using previously published literature from the Scopus database that incorporates PCM in solar still desalination. The results highlight five critical parameters for evaluation: physical properties, chemical properties, thermal properties, kinetic properties, and economic cost. For optimal compatibility with tropical environments, paraffin wax and soybean wax are the most appropriate choices, whereas coconut oil and beef tallow, which melt faster than wax, are better suited for subtropical regions.